AB1153 ANALGESIC AND ANTI-INFLAMMATORY DRUG USE IN PATIENTS WITH RHEUMATOID ARTHRITIS, PSORIATIC ARTHRITIS AND SPONDYLOARTHRITIS VERSUS CONTROLS IN A BELGIAN GENERAL PRACTITIONER REGISTRY. (2nd June 2020) - Pazmino, S.; Stouten, V.; Verschueren, P.; Mamouris, P.; Westhovens, R.; De Vlam, K.; Bertrand, D.; Van der Elst, K.; Vaes, B.; De Cock, D.
Abstract : Background: Rheumatoid arthritis (RA), psoriatic arthritis (PSA) and spondyloarthritis (SPA) are the most common inflammatory rheumatic diseases. Pain is the hallmark symptom in these conditions and pain relief is ranked first amongst preferred outcomes by patients. Level of analgesic and anti-inflammatory drug use is unknown in these populations in Belgium. Objectives: To compare analgesic and anti-inflammatory drug use in patient populations of RA, PSA and SPA versus controls in a General Practitioners (GP) setting in an era of expanding treatment possibilities in rheumatology. Methods: Data were obtained from Intego over a 13-year time interval from 1999 to 2012. Intego is a Flemish GP-based morbidity registration network hosted at the Academic Center for General Practice of the KU Leuven, covering 2% of the Flemish general population. Patients classified under the International Classification of Primary Care codes L88 (rheumatoid/seropositive arthritis) and L99 (musculoskeletal disease other) were selected for this study. Experienced rheumatologists verified if the keywords mapped to these codes corresponded to a diagnosis of RA/SPA/PSA. The date of these diagnoses in Intego was considered "baseline". Controls were matched on age, gender, baseline date and GP practice in a 4:1 case ratio. Intego registers all electronic drug prescriptions by the GP. Anytime use of glucocorticoids, NSAIDs, opioids except tramadol, tramadol and paracetamol in the first 3 years after diagnosis is presented. Proportions of patients and controls on analgesic and anti-inflammatory drugs were compared by Chi-Square analyses. Results: Over a 13-year period, 738, 229 and 167 patients were included with a diagnosis of RA, SPA or PSA, respectively. Table 1 presents the medication use of these populations. The three conditions had statistically significantly more prescriptions for all types of analgesic and anti-inflammatory drugs compared to controls. Approximately 70% of patients with an inflammatory rheumatic condition received mild pain medication (NSAIDs, Tramadol and Paracetamol) in the first three years after diagnosis. To note is the high use of opioids, even excluding tramadol, in these populations ranging up to 15%. Conclusion: Frequent analgesic and anti-inflammatory drug use in patients with a chronic inflammatory joint condition is to be expected, and underlined by the results of our study. Remarkably is the high use of opioids, even excluding tramadol, in patients with RA, PSA and SPA in an era of effective disease modifiers, as well in the control population. Our data shows that around 9% of the Belgian population receives at least once over a 3-year period an opioid prescription. As our data only registers electronic GP prescriptions, this is likely to be an underestimation of the true prescription proportion. Detailed analyses on dose and duration of analgesic and anti-inflammatory drugs will follow. Disclosure of Interests: Sofia Pazmino: None declared, Veerle Stouten: None declared, Patrick Verschueren Grant/research support from: Pfizer unrestricted chair of early RA research, Speakers bureau: various companies, Pavlos Mamouris: None declared, Rene Westhovens Grant/research support from: Celltrion Inc, Galapagos, Gilead, Consultant of: Celltrion Inc, Galapagos, Gilead, Speakers bureau: Celltrion Inc, Galapagos, Gilead, Kurt de Vlam Grant/research support from: Celgene, Eli Lilly, Pfizer Inc, Consultant of: AbbVie, Eli Lilly, Galapagos, Johnson & Johnson, Novartis, Pfizer Inc, UCB, Delphine Bertrand: None declared, Kristien Van der Elst: None declared, Bert Vaes: None declared, Diederik De Cock: None declared